Don't worry, bee happy - Burach, Ross (Acorn (Scholastic Inc.)., 2020)
Whether it is best friends picture day or the waggle dance, Bumble and Bee buzz around the pond, trying to engage Froggy in their playful activities--even coming up with a terrifying way to cure Froggy's hiccups.